Analisis Tingkat Percaya Diri, Kecerdasan Emosional, dan Kecerdasan Sosial Siswi Sekolah Dasar Berdasarkan Partisipasi Kegiatan Ekstrakurikuler - Putri Maharani; Wulandari Putri; Wildan Alfia Nugroho (Universitas Hamzanwadi, 2026)
The problem addressed in this study is the limited understanding of the psychological and social differences between elementary school girls who are active and those who are inactive in extracurricular activities. This study aims to analyze differences in the levels of self-confidence, emotional intelligence, and social intelligence among fifth- and sixth-grade elementary school girls based on their participation in extracurricular activities. The method used was a quantitative approach with an ex post facto design. A sample of 107 girls was selected using purposive sampling. Data collection was conducted using a structured questionnaire to measure the three variables. Data analysis included descriptive statistics, normality tests, homogeneity tests, and hypothesis testing using one-way ANOVA. The results showed significant differences in levels of self-confidence (p=0.004), emotional intelligence (p=0.003), and social intelligence (p=0.027) between the two groups. The effect sizes were in the moderate category for self-confidence and emotional intelligence (η² = 0.078 and 0.083), and in the small category for social intelligence (η² = 0.046). In conclusion, participation in extracurricular activities is associated with better psychological and social development among female students.